2005
DOI: 10.1128/iai.73.12.7844-7852.2005
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Activates Myosin Light-Chain Kinase To Disrupt Claudin-4 and Claudin-5 and Increase Epithelial Permeability

Abstract: Helicobacter pylori is a spiral, gram-negative bacterium that specifically and persistently infects the human stomach. In some individuals, H. pylori-induced chronic gastritis may progress to gastroduodenal ulcers and gastric cancer. Currently, the host-microbe interactions that determine the clinical outcome of infection are not well defined. H. pylori strains capable of disrupting the gastric epithelial barrier may increase the likelihood of developing serious disease. In this study, H. pylori strain SS1 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
93
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 53 publications
4
93
0
1
Order By: Relevance
“…The early period of increased paracellular permeability of [ 14 C]sucrose (24 h) correlated with not only reduced claudin-5 expression, but also with a decrease in its co-localization with ZO-1. Similar to these presented data, increased permeability has also been linked to a loss of claudin-5 expression and movement away from the junction in gastric epithelium (Fedwick et al, 2005). During the later period of disruption in paracellular transport, claudin-5 co-localized with ZO-1, but was also visible in a discontinuous and non-junctional pattern throughout the endothelial cell (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…The early period of increased paracellular permeability of [ 14 C]sucrose (24 h) correlated with not only reduced claudin-5 expression, but also with a decrease in its co-localization with ZO-1. Similar to these presented data, increased permeability has also been linked to a loss of claudin-5 expression and movement away from the junction in gastric epithelium (Fedwick et al, 2005). During the later period of disruption in paracellular transport, claudin-5 co-localized with ZO-1, but was also visible in a discontinuous and non-junctional pattern throughout the endothelial cell (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…For example, it has been reported that H. pylori was able to increase paracellular permeability by disrupting occludin, claudin-4, and claudin-5 [10], and Cdx2 was shown to play an important role in the regulation of intestinal claudin expression not only in gastric mucosa with intestinal metaplasia but also in gastric carcinoma [11]. Moreover, ALL-1 fusion partner from chromosome 6 (AF-6), which is a Ras target, interacts with ZO-1 [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have been reported regarding the biological functions of claudin-4 in gastric cancer. For example, it has been reported that Helicobacter pylori was able to increase paracellular permeability by disrupting occludin, claudin-4, and claudin-5 [10], and it has been shown that Cdx2 plays an important role in the regulation of intestinal claudin expression, not only…”
mentioning
confidence: 99%
“…Metastatic tumor cells must first breach the blood-brain barrier (BBB), 3 which acts as a selective interface between the peripheral circulation and the central nervous system. BBB is a unique anatomical structure that is mainly constructed by tight junctions between the brain endothelial cells and pericytes that are embedded in the basement membrane of the endothelial cells (2)(3)(4)(5)(6)(7)(8). The tight junction confers low paracellular permeability and high electrical resistance, making the barrier function 50 -100 times tighter than peripheral microvessels (9).…”
mentioning
confidence: 99%